2008
DOI: 10.1159/000128269
|View full text |Cite
|
Sign up to set email alerts
|

Organic Elemental Composition in Fingernail Plates Varies between Sexes and Changes with Increasing Age in Healthy Humans

Abstract: Background: Keratin, an α-helical fibrous protein, is the primary component of human nail plates. No data on age-related changes in healthy subjects are present. Objective: This study investigated whether keratin amount and composition, as indicated by organic elemental composition of fingernails, varies with aging and between sexes. Methods: Nail clippings from 225 healthy individuals (93 males, 132 females), aged 20–90 years, were analyzed for carbon (C), nitrogen (N), and sulfur (S) contents with an automat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 36 publications
2
19
0
1
Order By: Relevance
“…Concentrations of C and Sr are equal within the experimental error in both groups. Dittmar et al 21 reported that carbon content in male and female subjects was not different, which is in accordance with our analysis. In 1988, Takagi et al detected 18 elements in human nails by argon inductively coupled plasma emission spectroscopy.…”
Section: Human Fingernail Spectrumsupporting
confidence: 93%
See 2 more Smart Citations
“…Concentrations of C and Sr are equal within the experimental error in both groups. Dittmar et al 21 reported that carbon content in male and female subjects was not different, which is in accordance with our analysis. In 1988, Takagi et al detected 18 elements in human nails by argon inductively coupled plasma emission spectroscopy.…”
Section: Human Fingernail Spectrumsupporting
confidence: 93%
“…As the age increases, the overall carbon level in the fingernails increases, although there are slight fluctuations. This was also observed by Dittmar et al 21 They performed analysis on 225 individuals (93 males and 132 females). Takagi et al reported that Al concentration decreased with age, which is not exactly in accordance with our results.…”
Section: Human Fingernail Spectrumsupporting
confidence: 74%
See 1 more Smart Citation
“…3b), containing C (80.00%) as the dominant element, as well as O (12.99%), N (6.06%), Na (0.37%), Si (0.10%), S (0.21%), and Ca (0.27%). The concentration of Na was increased in the damaged nail, Al was absent (possibly correlated with the less hardening nail) [32], whereas the concentrations of Si and S were low. The diminished content of S in the injured nail may be explained by the action of chemical compounds that can cause the destruction of the nail, attacking the disulfide bridges, which are responsible for the stability of keratin nail matrix (fig.…”
Section: Discussionmentioning
confidence: 99%
“…Mean carbon content in the fingernails of healthy adults is 45% and increases with aging. Females have more sulfur and less nitrogen, but the sulfur content does not change with aging (Dittmar et al, 2008). Understanding the structure and properties of the nail plate is fundamental for the development of potent drugs, which can be used in the treatment of nail diseases.…”
Section: Introductionmentioning
confidence: 99%